Risk of Erectile Dysfunction After Traumatic Brain Injury: A Nationwide Population-Based Cohort study in Taiwan. Issue 4 (July 2018) - Yang, Yun-Ju; Chien, Wu-Chien; Chung, Chi-Hsiang; Hong, Kun-Ting; Yu, Yi-Lin; Hueng, Dueng-Yuan; Chen, Yuan-Hao; Ma, Hsin-I; Chang, Hsin-An; Kao, Yu-Chen; Yeh, Hui-Wen; Tzeng, Nian-Sheng
Introduction: In our study, we aimed to investigate the association between a traumatic brain injury (TBI) and subsequent erectile dysfunction (ED). This is a population-based study using the claims dataset from The National Health Insurance Research Database. Methods: We included 72, 642 patients with TBI aged over 20 years, retrospectively, selected from the longitudinal health insurance database during 2000–2010, according to the ICD-9-CM. The control group consisted of 217, 872 patients without TBI that were randomly chosen from the database at a ratio of 1:3, with age- and index year matched. Cox proportional hazards analysis was used to estimate the association between the TBI and subsequent ED. Results: After a 10-year follow-up, the incidence rate of ED was higher in the TBI patients when compared with the non-TBI control group (24.66 and 19.07 per 100, 000, respectively). Patients with TBI had a higher risk of developing ED than the non-TBI cohort after the adjustment of the confounding factors, such as age, comorbidity, residence of urbanization and locations, seasons, level of care, and insured premiums (adjusted hazard ratio (HR) = 2.569, 95% CI [1.890, 3.492], p < .001). Conclusion: This is the first study using a comprehensive nationwide database to analyze the association of ED and TBI in the Asian population. After adjusted the confounding factors, patients with TBI have a significantly higher risk of developing ED, especially organic ED, than the general population. This finding might remind clinicians that it's crucial in early identification and treatment of ED in post-TBI patients.